College Students' Open Educational Resources (OER) Experience and Their Perceived Attributes: A Study from Zhejiang University - Li, Yan; Hu, Ermei (International Journal of Emerging Technologies in Learning (iJET), 2013)
The purpose of this study was to investigate Chinese college studentsâ?? experience of and their perceived attributes of Open Educational Resources (OER). Students from Zhejiang University were selected as target population. A two-part questionnaire was developed and randomly sampling was used to collect data. The results of data analysis found that: three fourth of participating students had OER usage experience; students tended to have strong agreement with perceived relative advantage and compatibility of OER, while studentsâ?? perceived trialability, complexity and observability of OER are not satisfactory; gender has no significant influence on college studentsâ?? perceptions about all of the five attributes of OER, while having OER usage experience or not would significantly impact on studentsâ?? perception about attributes of OER. Based on the findings, the study concluded by putting forward some suggestions.